PREPARING EXERCISES USING AUXILIARY TRAINING TOOLS TO ENHANCE AGILITY AND SPEED OF MOVEMENT AND THEIR IMPACT ON CERTAIN COMPLEX OFFENSIVE SKILLS IN BASKETBALL FOR PLAYERS UNDER 18 YEARS OLD - Dr. Mustafa Khorsheed Ahmed (Scholars Digest Publishing, 2025)
The aim of this study was to prepare specific exercises using auxiliary training tools for basketball players under 18 years old to enhance agility and speed of movement, and to examine the impact of these exercises on certain complex offensive skills in basketball. The study hypothesized that there would be statistically significant differences between the pre-test and post-test results of the sample, and that exercises designed to improve agility and speed of movement using auxiliary training tools would positively affect the development of some complex offensive skills in basketball players under 18 years old. The researcher used the experimental method, which was suitable for the nature and problem of the study. The research sample consisted of fourteen players who were selected intentionally, with four players excluded for conducting the exploratory trial. The experimental group, consisting of ten players, performed the agility and speed training exercises, with a total of twenty-four training units divided over 8 weeks, with three training units per week. The exercises designed for agility and speed took 20 minutes per training unit. The researcher employed the interval training method, with both low and high-intensity sessions, ranging from 75% to 90% of the player's maximum capacity, using the principle of positive rest between exercises. The load structure followed a wave-like pattern across the weeks. The study concluded that the specific exercises and the auxiliary training tools used by the researcher were effective in improving agility and speed of movement. Additionally, the development of physical variables through these exercises had a positive impact on the development of complex offensive skills in basketball players under 18 years old. The interval training method, both low and high intensity, played a key role in improving the physical variables and complex offensive skills studied. Based on the findings, the researcher recommends the following: • It is essential to focus on agility and speed exercises during training sessions, as they play a significant role in improving complex offensive skills. • Continuous use of auxiliary training tools during training sessions is recommended to maximize physical and skill development. • The use of both low and high-intensity interval training should be emphasized in training units, as this has a crucial role in enhancing physical variables and the complex offensive skills under study
Keywords: interval – agility – tools – auxiliary – complex.